Design of a Television Viewer Safe Distance Control Device for Children Ages 5 to 10 Years Using Arduino Uno with Motion Sensor and Proximity Sensor - Imam Faizal; Samsul Arifin (Procedia of Engineering and Life Science, 2021)
When a child is 5 to 10 years old, it is very vulnerable to experience impaired health. One of them is vision. Vision is the main source that is very useful for life. A mother is worried when her children are constantly watching television. The anxiety will increase when children watch their favorite shows on television is very closely distance. From the description of the problem above, the writer found an idea to make a tool that can remind young children to maintain their visibility while watching television. The tool uses an Arduino Uno microcontroller coupled with a distance sensor and a motion sensor. When the sensor detects humans are closed to the television, then the tool will give a warning through the speaker in the form of sound. From the results of research when the sensor detects the distance between humans and the television is too close, the device will warn by making noise from the speakers. After 20 trials, data was obtained that 17 times the device is successfully detected movement via sensor and could give a warning to television viewers. Hope with the creation of a television viewers safe space can help parents to reduce anxiety when children watch television